PROJECT-BASED LEARNING CONTAINS SUSTAINABLE DEVELOPMENT GOALS: THE EFFORTS TO IMPROVE STUDENTS’ SUSTAINABILITY AWARENESS - Widya Eko Nurazizah; Widi Purwianingsih; Rini Solihat; Indri Andriyatno; Dwi Nining Lestari (EDUSAINS, 2024)
Students have a sustainability awareness level from a lack of knowledge, attitude, and behaviour. The purpose of this study is to implement SDGs-contained PjBL on Biotechnology material as one of the efforts to improve the students’ sustainability awareness. The research method is a quasi-experiment by nonequivalent control group design. The research sample is 32 students of the control class and 34 students of the experiment class of class-XII Senior High School. The data-collecting technique is using questionnaires and learning observations. The sustainability awareness questionnaire has 18 question items and consists of three indicators i.e., sustainability knowingness, sustainability attitudes, and sustainability behaviour adapted from the Sustainability Consciousness Questionnaire Short (SCQ-S). The data analysis uses an Independent Sample T-test and N-Gain Test. The result of the Independent Sample T-Test shows not that much significant difference between the experiment and control classes' pretest average (0,509 > 0,025). The experiment and control classes' posttest average results show not that much significant difference (0,000 < 0,025). The N-Gain score result of the experiment class shows students’ sustainability awarenessimprovement after conducting SDGs-contained PjBL in the medium category (N-Gain = 0,4869). The improvement follows the result of SDGs-contained PjBL implementation on 93% of teachers, and 90,96% of students in the excellent category. These research findings are obtained through SDGs-contained PjBL, students’ sustainability knowingness, and sustainability attitudes, especially on the social dimension which experiences higher improvement.